PERSEPSI MAHASISWA PROGRAM STUDI TATA BOGA TERHADAP PELUANG BISNIS DI SEKTOR PARIWISATA - Ni Putu Oka Ariantini; Bagus Putu Eka Dharma Susila (Journal Research of Management, 2026)
ABSTRACT   This study aims to analyze the perceptions of Culinary Arts Study Program students toward business opportunities in the tourism sector. The study employed a qualitative method with a descriptive approach. The informants of this study were students of the Culinary Arts Study Program at Akademi Komunitas MAPINDO selected through purposive sampling. Data were collected through interviews and documentation. The collected data were analyzed using descriptive qualitative analysis through data reduction, data presentation, and conclusion drawing. The findings revealed that students had positive perceptions regarding business opportunities in the tourism sector. Students believed that the development of tourism creates significant opportunities for culinary businesses, cafés, restaurants, catering services, and other creative food-related businesses. In addition, digital technology and social media were perceived as important tools for promoting and developing businesses more effectively. Students’ perceptions were influenced by practical learning experiences, entrepreneurial motivation, creativity, and skills obtained during the learning process. However, several challenges were also identified, including limited capital, business competition, and changing consumer preferences. This study is expected to contribute to the development of entrepreneurship education, particularly for Culinary Arts students in preparing them for business opportunities in the tourism sector.